Exploring the Links between Genetics and Diseases: Review - Umaru, Isaac John; Esseyi, Chabunda Endashi; Umaru, Kerenhappuch Isaac; Tensaba, Akafa Andes; Istifanus, Dafup Kadel; Umahi, David (Darul Yasin Al Sys, 2024)
This review article delves into the intricate connections between genetics and diseases, exploring how genetic variations influence the development and progression of various health conditions. The paper provides a comprehensive overview of the latest research in the field of genomics, highlighting key discoveries that have advanced our understanding of the genetic underpinnings of diseases. We examine both monogenic and polygenic disorders, illustrating how mutations in single genes or complex interactions among multiple genes contribute to disease phenotypes. Furthermore, the review discusses the role of epigenetics and gene-environment interactions in modulating disease risk and expression. By synthesizing current findings, this article underscores the potential of genetic research in paving the way for personalized medicine and targeted therapies, offering new avenues for diagnosis, treatment, and prevention of genetic diseases. The review also addresses the ethical and societal implications of genetic research, emphasizing the importance of responsible scientific practices and equitable access to genetic advancements.